Vinayagar and Tamil Medicine - Rangarajan, G (Sakha: Multidisciplinary Journal of Science, Art & Technology, 2025)
Vinayagar, also known as Ganesha, is a prominent deity in Hinduism, venerated primarily in South India. His significance extends beyond spirituality; he is often associated with knowledge, wisdom, and the removing obstacles. This paper explores the connections between Vinayagar and Tamil medicine, focusing on the integrating spiritual practices, herbal medicine, and traditional healing systems prevalent in Tamil culture. Additionally, it investigates how these elements reflect the socio-cultural ethos of Tamil society and their relevance in contemporary health practices.
Keywords: Vinayagar; Herbals; Tamil Medicine; Benefits; Tamil Culture; Spiritual Practices